Factors Affecting Quality of Life of People with Coronary Heart Disease at Puskesmas Sikumana Kupang City - Gadur Blasius; Fransiskus Salesius Onggang; Aben BYH Romana; Olvian Maraweli; Antonia Helena Hamu (Eduvest - Journal of Universal Studies, 2023)
Coronary heart disease is a disease caused by flak that accumulates in the arteries which reduces the supply of oxygen throughout the body, especially the heart muscle. A good quality of life in patients with coronary heart disease is needed to maintain that patients are able to get the best health status, optimally and for as long as possible. The study aims to find out the Factors Affecting the Quality of Life of Patients with Coronary Heart Disease at the Sikumana Health Center. A quantitative descriptive research method using a cross sectional approach. The results of the 3 variables showed that depression had a significant relationship to quality of life p-value = 0.028, coping had no effect on the quality of life of heart sufferers p-value = 0.078 and family support no effect on the quality of life of people with heart disease with p-value = 0.101, multiple multivariate analysis with the backward LR method, it can be seen that the R Square value is 0.335 meaning that coping and family support variables explain the quality of life of heart patients by 33.5% while the rest is explained by other variables not examined in this study. based on the beta coefficient, the independent variable that has the greatest beta coefficient value is family support (coef. beta = -1.867). It can be concluded that the independent variable that has the most influence on the quality of life of heart sufferers is family support